Mekhman Suleimanovich Yusubov - Article Editorial (Бюллетень сибирской медицины)
The creative biography of Professor M.S. Yusubov, prominent scientist, head of Chemistry Chair of Siberian State Medical University is presented, his main trends of scientific and public activity are concerned.